EFFECT OF POLLUTION ON THE THREADFIN BREAM NEMIPTERUS JAPONICUS IN THE HARBOUR WATER OF VISAKHAPATNAM - T. C. DIANA; C. MANJULATHA (The Bioscan, 2012)
In the present study, Nemipterus japonicus were collected from polluted harbour water of Visakhapatnam and found many zoonotic diseases which become major threat to human health. The diseases observed in this study are exophthalmia, skin discoloration with deep ulcers, frayed fins, damaged gills, distended abdomen with calcified gonads and a large polypoidal mass in the buccal cavity of N. japonicus. The results suggest that when such fish is consumed by humans, it may lead to many health problems